Nomograms forecasting long‐term overall and cancer‐specific survival of patients with oral squamous cell carcinoma. (7th March 2018) - Wang, Fengze; Zhang, Hui; Wen, Jiao; Zhou, Jun; Liu, Yuan; Cheng, Bingkun; Chen, Xun; Wei, Jianhua
Abstract: Our aim was to establish a "nomogram" model to forecast the overall survival (OS) and cancer‐specific survival (CSS) of oral squamous cell carcinoma (OSCC) patients. The clinicopathological data for the 10, 533 OSCC patients were collected from the Surveillance, Epidemiology and End Results (SEER) database. We used a credible random split‐sample method to divide 10, 533 patients into two cohorts: 7046 patients in the modeling cohort and 3487 patients in the external validation cohort (split‐ratio = 2:1). The median follow‐up period was 32 months (1–119 months). We developed nomograms to predict 5‐ and 8‐year OS and CSS of OSCC patients with a Cox proportional hazards model. The precision of the nomograms was assessed by the concordance index (C‐index) and calibration curves through internal and external validation. The C‐indexes of internal validation regarding 5‐ and 8‐year OS and CSS were 0.762 and 0.783, respectively. In addition, the external validation's C‐indexes were 0.772 and 0.800. Based on a large‐sample analysis targeting the SEER database, we established two nomograms to predict long‐term OS and CSS for OSCC patients successfully, which can assist surgeons in developing a more effective therapeutic regimen and conducting personalized prognostic evaluations. Abstract : We successfully established two nomograms predicting overall survival(OS) and cancer‐specific survival(CSS) of OSCC patients collected from SEER database. The validation results of the nomograms through the concordance index (C‐index) and calibration curves showed that the model were credible, which can assist surgeons in developing a more effective therapeutic regimen and conducting personalized prognostic evaluations.